2017
DOI: 10.1007/s00595-017-1618-3
|View full text |Cite
|
Sign up to set email alerts
|

Nectin-1 expression in cancer-associated fibroblasts is a predictor of poor prognosis for pancreatic ductal adenocarcinoma

Abstract: Diffuse nectin-1 expression in the CAFs of PDAC patients is associated with invasion, metastasis, and shorter survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…CAFs express various unique proteins, which are related to the prognosis of PDAC. For example, nectin cell adhesion molecule 1 (NECTIN1) + CAFs were an independent prognostic factor in PDAC [ 66 ]. The level of NECTIN1 in the CAFs of PDAC patients was positively correlated with advanced tumor stage ( P = 0.016), PNI ( P = 0.022), and short OS ( P = 0.003) [ 66 ].…”
Section: Cellular Mediators Of Pnimentioning
confidence: 99%
See 1 more Smart Citation
“…CAFs express various unique proteins, which are related to the prognosis of PDAC. For example, nectin cell adhesion molecule 1 (NECTIN1) + CAFs were an independent prognostic factor in PDAC [ 66 ]. The level of NECTIN1 in the CAFs of PDAC patients was positively correlated with advanced tumor stage ( P = 0.016), PNI ( P = 0.022), and short OS ( P = 0.003) [ 66 ].…”
Section: Cellular Mediators Of Pnimentioning
confidence: 99%
“…For example, nectin cell adhesion molecule 1 (NECTIN1) + CAFs were an independent prognostic factor in PDAC [ 66 ]. The level of NECTIN1 in the CAFs of PDAC patients was positively correlated with advanced tumor stage ( P = 0.016), PNI ( P = 0.022), and short OS ( P = 0.003) [ 66 ]. Fibroblast activation protein alpha was a broad marker of CAFs in various cancers and was closely associated with PNI ( P = 0.009), tumor size ( P < 0.001), and poor prognosis ( P = 0.0085) in PDAC patients [ 67 ].…”
Section: Cellular Mediators Of Pnimentioning
confidence: 99%
“…In breast cancer metastatic tumors have increased expression of nectin-1 and nectin-2 [85]. In pancreatic tumors, overexpression of nectin-1 correlates with poor prognosis of the disease [86]. In such pathological situations, nectin-1 could be a target of choice for NK cells aiming at eliminating cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, silencing of Nectin-1 affected the expression of epithelial genes suggesting not only a structural role of Nectin-1 but also a role as a mediator of gene regulation [37]. A recent study [33] proposed Nectin-1 as a novel regulator of the tumor microenvironment of pancreatic ductal adenocarcinoma by demonstrating aggressive clinical features and a significant poor overall survival when Nectin-1 is expressed in cancer-associated fibroblasts. Consequently, Nectin-1 positive cells are either cancer cells or cells of the tumor microenvironment and appear to harbor properties of progenitor/stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nectin-1, in particular, regulates axo-glial interactions, Schwann cell differentiation, and myelination [30-32]. Substantial data [33] arising from other studies have demonstrated that expression of Nectin-1 in case of specific malignant tumors is associated with aggressive tumor phenotypes.…”
Section: Introductionmentioning
confidence: 99%